Design and design of animaker-based video learning media on planet characteristics material to improve primary school students' understanding of science concepts - Aisyah, Siti; Kelana, Jajang Bayu; Kurnia Jayadinata, Asep (Sekolah Pascasarjana UPI, 2023)
The real problem is that some of the teachers only carry out learning activities using conventional methods. Learning is carried out using the lecture method without using learning media. Students only focus on teacher explanations and books because of the lack of facilities and infrastructure. The results of this study are to produce a product that is feasible, effective and facilitates students. The method used in this research is the research and development. Respondents to this research were Grade 6 students. This research led to and produced 1) The development process, the first stage was a literature review and data collection through interviews to explore the potentials and obstacles in the science learning process as well as to make designs and initial product designs. 2) Producing a product in the form of Animaker-based learning media that can help increase student motivation in learning material about the solar system, a feasible product can be seen from the results of the value by the validator. 3) This learning media is well received by students, this can be seen from the results of the student response questionnaire which scores an attractive category. 4) Animaker-based learning media can optimize the ability of science concepts. Increasing student learning outcomes in the realm of knowledge obtains a gain value of 1.00, which means an increase in learning outcomes in the cognitive domain of the high category on a wide-scale test.